2020
DOI: 10.1007/s11187-020-00379-z
|View full text |Cite
|
Sign up to set email alerts
|

Does external R&D matter for family firm innovation? Evidence from the Italian manufacturing industry

Abstract: This article focuses on the relationship between external research and development (R&D) and firm innovation output. Using a sample of Italian manufacturing firms in the period of 2007-2009, the role played by external R&D is evaluated, investigating differences between family and non-family firms. Results show that the R&D acquired from external sources has a positive impact, especially on family firms, suggesting that family companies have a greater capacity to translate external R&D into tangible economic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 100 publications
2
38
1
Order By: Relevance
“…Additionally, this study may also offer some important suggestions to policymakers for the design of new policies and incentives aimed at boosting product innovation efficiency in family firms. For instance, they should foster the development of collaboration relationships between family firms and different partner types by offering incentives for the SEW protection and should facilitate the access of family firms to new knowledge on this subject by strengthening family business' professional associations and networks (Aiello et al , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this study may also offer some important suggestions to policymakers for the design of new policies and incentives aimed at boosting product innovation efficiency in family firms. For instance, they should foster the development of collaboration relationships between family firms and different partner types by offering incentives for the SEW protection and should facilitate the access of family firms to new knowledge on this subject by strengthening family business' professional associations and networks (Aiello et al , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that innovation in the context of FFs is characterized by a paradox: that is, FFs innovate less despite having the ability to do more (De Massis et al, 2015). Specifically, although their higher flexibility and their longer-term perspective would be in itself factors conducive to innovation, FFs are less willing to innovate due to their risk aversion, lack of resources and knowledge, and reluctance to ask for external financial investments (Aiello, Cardamone, et al, 2020). Additionally, some studies highlighted that FFs achieve higher innovation outputs compared with non-family firms (Duran et al, 2016), whereas others found that the returns to their R&D investments are low .…”
Section: Eco-innovation In Family Firmsmentioning
confidence: 99%
“…Across the world, family firms (FFs) dominate the structure and output of many economies (Xi et al, 2015;Basly and Hammouda, 2020) but many aspects of their behaviour remain unexplored (Aiello et al, 2020). One such area is FFs innovation behaviour (De Massis et al, 2013;Alrubaishi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…According to KPMG (2017) innovation is among the top three concerns of FFs. Yet, family variables are rare in the mainstream innovation studies (Calabro et al, 2019;Aiello et al, 2020) and FFs literature paid little attention to innovation (Kraus et al, 2012;De Massis et al, 2013;Camison Zornoza et al, 2020). Moreover, FFs literature is mostly focused on Western European (Classen et al, 2014;Nieto et al, 2015;Sciascia et al, 2015;Camison Zornoza et al, 2020) or U.S. contexts (Zahra et al, 2004;Zahra, 2005;Block et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation